Implementation of Generate and Test Algorithm for Junior High School Zoning System in Malang - Ratnasar, Novia; Agustin Mawarni, Inggar Tri; Nur Handayani, Anik; Wibawa, Aji Prasetya; Hammad, Jehad A. H; Wibowotomo, Budi; Sugandi, Machmud (2020 4th International Conference on Vocational Education and Training (ICOVET), 2020)
Admission of new students in 2019 through zoning still faces many obstacles, one of which is the readiness of the application to determine the distance of a student's house from the nearest recommended school. The purpose of this study is to provide better recommendations regarding the shortest and most accurate distance in the zoning system for admission of junior high school students in Malang by using the Generate and Test algorithm without having to do it manually or using other map applications. The results of this study indicate that the distance value obtained from the haversine formula corresponds to the original distance measured through a zoning application that applies the Generate and Test algorithm to measure the closest distance from the student's location. The recommended distance is given through a process of repetition and comparison of nodes. By using the generate and test algorithm for the search process the shortest distance from the user to the destination school has an average time of 6.2MB, the level of accuracy is the same as the Haversine calculation.